Peningkatan Densitas Energi Formula Enteral untuk Diabetes Melitus Menggunakan Jewawut (Setaria italica) dan Lele (Clarias gariepinus) - Vania Alvabella Wijaya; Yohanes Kristianto (Media Gizi Kesmas, 2026)
Background: The low energy density of enteral formulas for Diabetes Mellitus (DM) poses a challenge to nutrition services. With the increasing prevalence of diabetes, meeting the nutritional needs of patients through enteral feeding is important to prevent complications. An alternative solution can be found by utilizing local foods such as foxtail millet and catfish. Objectives: To increase the energy density of enteral formulas using foxtail millet and catfish. Methods: The enteral formula was developed by adjusting the composition of the ingredients to meet nutritional standards. The comparison of the use of foxtail millet flour and catfish flour was composed of levels, namely F1 (45:10), F2 (50:5), F3 (50:10), and F4 (55:5). The research activities included product formulation, flowability test, viscosity test, organoleptic test, Color Difference Ratio (CDR) test, best treatment level selection using Metode Perbandingan Eksponensial (MPE), and proximate and dietary fiber test. Data analysis was performed using univariate (descriptive test), normality (Shapiro-Wilk), and bivariate (Kruskal-Wallis) tests. Results: The energy density of the developed formulas ranged from 1.01 to 1.03 kcal/ml, with nutritional content proportions in accordance with the standards. All developed formulas could flow through the Nasogastric Tube (NGT) within 7–9 s with viscosity ranging from 14.30 to 16.35 mPa’s. The organoleptic test showed significant results for the aroma parameter (p=0.037). CDR testing showed that F3 had the darkest color, whereas F2 had the lightest color. Based on the best treatment level test, the selected formula was F4, as it was able to flow through the NGT in 8.18 s with a viscosity of 14.5 mPa's. F4 contained 756.80 kcal energy, 18.61 g protein, 10.81 g fat, 147.67 g carbohydrates, 7.86 g fiber, 20.90% moisture, and 6.71% ash per 100 g. Conclusion: The EN-JEWEL enteral formula, particularly F4 (55:5), has the potential to increase the energy density.